Genotype by environment interaction and stability analysis using SREG stability statistics for yield and yield attributing traits in rice - Jambhulkar, Nitiprasad Namdeorao; Bose, Lotan Kumar; Pande, Kanailal; Singh, Onkar Nath (ORYZA-An International Journal of Rice, 2019)
Stability of performance is one very important criteria for plant breeders especially under the rapidly changing environments of growing the crops. SREG analysis is an efficient methodology for genotype × environment interaction and stability analysis. But, the model does not provide quantitative stability measure. Hence, two new stability statistics SREG Stability Index I (SRSI I) and SREG Stability Index II (SRSI II) are proposed to quantify and rank the genotypes. The field experiments were conducted with nine rice genotypes in a randomized complete block design with three replications under boro condition for four consecutive years (2009-2012). Grain yield and other yield attributing traits (days to 50% flowering, plant height, ear bearing tillers, grains per panicle and thousand grain weight) were recorded. The combined analysis of variance revealed that environment effect was significant for four out of six traits. Genotypic effect was significant for all traits. Three traits showed significant genotype × environment interaction effect. SRSI I and SRSI II were computed and ranking was done for all the traits. Annada was best genotype for grain yield, thousand grain weight and days to 50% flowering. Satabdi, WITA12 and Ratna were best genotypes for grains per panicle, ear bearing tillersand plant height respectively.